The Effect of Continuous Theta Burst Stimulation over the Right Dorsolateral Prefrontal Cortex on Cognitive Function and Emotional Regulation in Patients with Cerebral Small Vessel Disease - Pei Dai; Zhao-Xia Wang; Hui-Xian Yu; Chang-Bin Liu; Si-Hao Liu; Hao Zhang (Brain Sciences, 2023)
Objectives: Cognitive impairment in cerebral small vessel disease (CSVD) is a common cause of vascular dementia and is often accompanied by mental disorders. The purpose of this study was to investigate the effect of continuous theta burst stimulation (cTBS) over the right dorsolateral prefrontal cortex (DLPFC) on the cognitive function and Hamilton depression (HAMD) scores in patients with CSVD. Methods: A total of 30 CSVD patients who met the inclusion criteria were randomly assigned to either the sham or cTBS group. The patients in both groups received routine cognitive function training. All the patients were under treatment for 14 sessions, with one session per day (each cTBS conditioning session consisted of three-pulse bursts at 50 Hz repeated at 5 Hz, 80% MT, and 600 pulses). Before and after the treatment, the patients in both groups were evaluated using the Montreal Cognitive Assessment (MoCA), Stroop Color-Word Test (SCWT), Trail Marking Test (TMT), Digital Span Test (DST), and HAMD test. The time to complete the SCWT and TMT were recorded. The scores of the MoCA, DST and HAMD test were recorded. Results: The HAMD scores in the cTBS group decreased significantly compared to the control (p < 0.05). There were no significant differences in the MoCA (including the MoCA subitems) or DST scores or in the SCWT or TMT completion times between the two groups (p > 0.05). For the HAMD scores and the MoCA subitem visuospatial/executive scores, the SCWT-B and SCWT-C completion times in the two groups both improved significantly before and after treatment (p < 0.05). For the MoCA scores, the DST-backward scores and the TMT-B completion times in the cTBS group improved significantly before and after treatment (p < 0.05). There was no significant difference in the SCWT-A, TMT-A completion times and MoCA subitems naming, attention, language, abstraction, delayed recall, and orientation scores either before or after treatment in the two groups or between the two groups (p > 0.05). Conclusions: In this study, cTBS over the right DLPFC decreased the HAMD scores significantly in patients with CSVD but had no significant improvement or impairment effects on cognitive function. cTBS over the right DLPFC could be used to treat CSVD patients with depression symptoms.